Design of an Isolated Parking Area and Its Impact on Air Traffic Services at Soekarno-Hatta International Airport - Slamet Riyanto; Susi Suhardianti; Imam Sonhaji (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Soekarno-Hatta International Airport is Indonesia’s busiest air hub, requiring effective ground traffic management to ensure operational safety and efficiency. One of the critical facilities supporting airport safety is the Isolated Parking Area (IPA), designated for aircraft facing emergencies such as bomb threats, fuel leaks, or hazardous material incidents. This study aims to analyze the design and operational placement of the IPA at Soekarno-Hatta International Airport in relation to air traffic flow and safety services, assessing its compliance with ICAO Annex 14 and Doc 9137 Airport Services Manual standards. Using a qualitative descriptive method with field observations, interviews, and document analysis, the research evaluates the existing location of the IPA on Taxiway WC1. Findings indicate that while the current IPA meets basic safety distance and design requirements, its proximity to main taxi routes creates operational bottlenecks and reduces ground movement efficiency during emergency activation. The study proposes relocation of the IPA to the EC2 area, which offers better spatial separation, direct access routes, and improved safety coordination without disrupting regular aircraft movement. This design adjustment is expected to enhance both airside safety and traffic flow efficiency, aligning with ICAO’s “Five Objectives” principles, particularly in maintaining and expediting the flow of air traffic. The research underscores that an optimal IPA design must integrate safety, accessibility, and operational continuity to support the sustainable development of Indonesia’s primary international gateway